دراسة التحليل المسبق لدقة المضلعات المساحية وبرمجته - ندى محفوض (Tishreen University, 2019)
تستخدم المضلعات كثيراً في الحياة المساحية العملية، و لذلك تمَّ التركيز في هذا البحث على دراسة التحليل المسبق لدقة المضلعات وذلك باستخدام قانون انتشار الأخطاء من أجل حساب الخطأ المتوسط التربيعي لكل من الزوايا والمسافات التي تحدّد مواصفات الأجهزة المساحية المستخدمة في القياس ( التيودوليت للزوايا وقائس المسافات الإلكتروني للمسافات ). و من ثم برمجة هذه الدراسة باستخدام لغة البرمجة Visual Pascal والحصول على برنامج ذو واجهة تخاطبيه يساعد في إنجاز التحليل المطلوب بسرعة كبيرة و دقة عالية ويتميز بسهولة الفهم والاستخدام. The Traverses are often used in the practical surveying domain. Therefore, in this research there is concentration on the  pre-analysis of Traverses accuracy, by applying error propagation law in calculating the square average error of the angles and distances that determine the specifications of the surveying instruments used in measurement (theodolite for the angles and the electronic meter for the distances). Then, the research moves to the programming of this study by using Visual Pascal language, to obtain an interactive interface that helps in achieving the required analysis with great speed and high accuracy, distinguished by easy understanding and usage.